Joyce’s Odyssey. A celebration of human ingenuity in Ulysses and an indictment of the mediocrity of generative AI (Journal of Applied Learning and Teaching, 2024)
This editorial reflects on James Joyce’s modernist novel Ulysses, first published 100 years ago in 1922. We reconstruct Ulysses’s revolutionary redefinition of the novel genre, its critical reception, and the immense challenges Joyce faced in writing, printing, and publishing the work. Narrating the genesis of Ulysses is a celebration of human ingenuity and perseverance in the face of daunting obstacles. We contrast Joyce’s brilliant literary achievement with the comparatively inferior outputs of much-hyped generative artificial intelligence (GenAI) chatbots. We discuss how the excessive caution and censorship exhibited by leading generative AI systems like ChatGPT undermine the free exchange of ideas, in stark contrast to the liberation of expression embodied by Ulysses. Finally, we consider the implications of these insights for effective teaching practices and visionary leadership in higher education, emphasising the vital role of cultivating broad intellectual engagement and critical thinking skills among students and faculty. Our editorial also provides an overview of the many human-created gems in our latest journal issue.